Assessing the status of patients with rheumatoid arthritis: modern tendencies - A. M. Lila; Yu. A. Olyunin; A. V. Gordeev (Современная ревматология)
Assessing the status of a patient with rheumatoid arthritis allows one to obtain information necessary to choose appropriate management tactics for the patient. The use of quantitative methods in routine practice to determine inflammatory activity is the basis for the development of standardized patient management recommendations and provides a substantial improvement in the quality of health care. At the same time, the accumulated experience suggests that the existing summary indices do not always allow one to correctly determine disease activity. The paper discusses factors that can corrupt the result of assessment of inflammatory activity, as well as approaches to eliminating possible errors.